Biogenesis of lysosome‐related organelles complex‐1 (BORC) regulates late endosomal/lysosomal size through PIKfyve‐dependent phosphatidylinositol‐3, 5‐bisphosphate. (19th August 2019) - Yordanov, Teodor E.; Hipolito, Victoria E. B.; Liebscher, Gudrun; Vogel, Georg F.; Stasyk, Taras; Herrmann, Caroline; Geley, Stephan; Teis, David; Botelho, Roberto J.; Hess, Michael W.; Huber, Lukas A.
Abstract: Mechanisms that control lysosomal function are essential for cellular homeostasis. Lysosomes adapt in size and number to cellular needs but little is known about the underlying molecular mechanism. We demonstrate that the late endosomal/lysosomal multimeric BLOC‐1‐related complex (BORC) regulates the size of these organelles via PIKfyve‐dependent phosphatidylinositol‐3, 5‐bisphosphate [PI(3, 5)P2 ] production. Deletion of the core BORC component Diaskedin led to increased levels of PI(3, 5)P2, suggesting activation of PIKfyve, and resulted in enhanced lysosomal reformation and subsequent reduction in lysosomal size. This process required AMP‐activated protein kinase (AMPK), a known PIKfyve activator, and was additionally dependent on the late endosomal/lysosomal adaptor, mitogen‐activated protein kinases and mechanistic target of rapamycin activator (LAMTOR/Ragulator) complex. Consistently, in response to glucose limitation, AMPK activated PIKfyve, which induced lysosomal reformation with increased baseline autophagy and was coupled to a decrease in lysosomal size. These adaptations of the late endosomal/lysosomal system reversed under glucose replete growth conditions. In summary, our results demonstrate that BORC regulates lysosomal reformation and size in response to glucose availability. Abstract : In this work, we present how late endosomal/lysosomal BLOC‐1‐related complex (BORC) regulates endosomal size through the regulation of the lipid kinase PIKfyve under cellular stress conditions. Phosphatidylinositol‐3, 5‐bisphosphate [PI(3, 5)P2 ] production is regulated through LAMTOR/Ragulator interacting BORC components (green). This process required AMP‐activated protein kinase (AMPK), a known PIKfyve activator, and was additionally dependent on the late endosomal/lysosomal adaptor, mitogen‐activated protein kinases and mechanistic target of rapamycin activator (LAMTOR/Ragulator) (blue) complex. Components of the BORC complex, namely Diaskedin and the anchor Myrlysin, act to suppress PIKfyve activation by AMPK. Upon removal of these components, AMPK can hyperactivate PIKfyve, which leads to increased PI(3, 5)P2 production. This is manifested by increased autophagosome generation and is functionally linked to tubule formation and the resulting reduction of endosomal size.